Mediating Role of Organizational Commitment between Perceived Organizational Support and Employee Perception in Public Sector Universities - Abideen, Zain-ul-; Rizvi, Syed Aamir Alam; Atiq , Nazia; Javed, Aisha (Pakistan Journal of Humanities and Social Sciences, 2023)
This research aims to examine the mediating role of organizational commitment between perceived organizational support and employees' perceptions of unethical pro-organizational behavior in public sector universities. The sample of 233 individuals from public sector universities in Sindh and Baluchistan was collected using non-probability purposive sampling. Data was collected using an adapted five-Likert scale questionnaire. The primary technique for data analysis was PLS-SEM using SMART-PLS 4.0. The findings demonstrated the critical role of organizational commitment in public sector institutions and how it acts as a bridge between perceived corporate support and employee perception. However, job security and organizational trust's moderating effects in the study were not substantiated. Public universities also face particular difficulties in creating an organizational commitment culture, which mediates employee perception and perceived support. Employees obey management's directives and stick to established procedures, which promotes growth and generates creative ideas. This study concludes that organizational commitment is crucial in public sector universities in mediating the relationship between perceived support and employee perception. It helps in growth constructively and fosters creativity. Perceived organizational support contributes to building commitment, and providing a supportive work environment, above all, it boosts employee well-being. The research's findings will be useful in policy and decision-making processes in public sector institutions.